Pengaruh Religiusitas, Kesadaran Halal, dan Alasan Kesehatan terhadap Keputusan Pembelian di Mcdonald’s Gresik Kota Baru - Dewantara, Ahmad Fajar (UPT Penerbitan Universitas Jember, 2023)
Allah SWT commands humans to always consume halal, healthy food and have complete faith in Allah SWT. The purpose of this study was to analyze the effect of religiosity, halal awareness, and health reasons on purchasing decisions at McDonald's GKB. The object of this research is the Muslim consumers of McDonald's Gresik Kota Baru with a total of 97 respondents using the incidental sampling technique. This study uses path analysis as an analytical tool. Based on the results of this study, religiosity has a positive effect of 1.5% but not significant on purchasing decisions, halal awareness has a positive effect of 1.3% but not significant on purchasing decisions, health reasons have a positive effect of 5.2% but not significant on purchasing decisions.